GAYA KOMUNIKASI PENYIAR RADIO TERHADAP MINAT DENGAR AUDIENS RADIO MEGASWARA - Wida Hartika; Halwa Nida Nur Syariah; Rachma Yuti Azmi; Nur Khalifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the communication style of radio broadcasters in influencing audience listening interest at Megaswara Radio. The background of this research is based on the strategic role of broadcasters as primary communicators who are capable of building emotional connections, creating an interactive atmosphere, and maintaining listener loyalty amid the competition of digital media.This study employs a qualitative approach with observation as the primary data collection technique. Observations were conducted on broadcasting activities, including the broadcasters’ speaking style, language use, intonation, and patterns of interaction with the audience during the program.The results indicate that communicative, persuasive, and personal communication styles are effective in attracting and maintaining audience listening interest. The use of casual language, variation in intonation, and responsive interaction are key factors in establishing closeness with listeners. Therefore, the communication style of radio broadcasters plays an important role in enhancing audience listening interest and the success of radio programs in Megaswara radio.